Neurally adjusted ventilatory assist in pediatric intensive care units: a systematic review and meta-analysis - Cai, Wenqian; Zuo, Yahui; Ma, Yan; Li, Mei; Li, Meng; Zhang, Lu (Frontiers in Pediatrics, 2025)
BackgroundPatient-ventilator asynchrony is a common problem in mechanical ventilation, leading to an increase in MV complications. Neurally adjusted ventilatory assist (NAVA) is a relatively new modality of mechanical ventilation that can be used for both invasive and non-invasive ventilation. There is evidence that NAVA reduces asynchronous events, but the sample size is small and the effect on specific physiological and clinical outcomes in children is controversial. Therefore, we conducted a systematic review and meta-analysis to evaluate the effect of NAVA on physiological parameters and clinical outcomes.MethodsWe searched electronic databases up to 26 September 2024. Clinical trials comparing NAVA with conventional mechanical ventilation modes were included. The primary outcomes were physiological parameters, respiratory parameters, ventilator-related parameters, and other clinical outcomes. Two review authors independently extracted data and assessed study quality using the Cochrane Risk of Bias tool2. The certainty of the evidence was assessed according to the scoring methodology. Apply meta-analysis as much as possible, and use qualitative analysis when conditions are not met.ResultsEleven studies involving 224 children met the inclusion criteria for this review. Four were randomized cross-over trials, three were prospective cross-over trials, and four were retrospective studies. There were significant differences in the methods and quality of the included studies. Meta-analyses revealed significant differences in PIP, RR, pO2, and the asynchronous index (AI) when compared to traditional modes of mechanical ventilation. However, no significant differences were observed in FiO2, PEEP, TV, pH, pCO2, SpO2, EAdimax, and EAdimin.ConclusionsThis systematic review and meta-analysis suggest that while NAVA has advantages for certain short-term physiological outcomes, the level of evidence remains low. Consequently, larger and higher-quality studies are necessary to identify potential short- and long-term differences between various ventilation patterns.